Hukum dan Etika Penggunaan AI di Era 4.0 - Nabila Nabila (Lembaga Pengembangan Kinerja Dosen, 2025)
The Era of the 4.0 Industrial Revolution has transformed various aspects of life, particularly with the advent of Artificial Intelligence (AI), which brings innovation and efficiency to sectors such as healthcare, education, and governance. However, the rapid development of AI also presents challenges related to law and ethics that must be addressed, such as legal responsibility for damages caused, secure management of personal data, and ethical boundaries regarding technological intervention. This article aims to discuss the legal and ethical issues surrounding the use of AI in Indonesia, focusing on the importance of developing an adaptive legal framework and the application of appropriate ethical principles. This research uses a normative research method with a regulatory approach and a conceptual approach. The discussion covers the definition of AI, legal and ethical challenges in its use, and recommendations for responsible technology implementation. The findings suggest that to ensure fair and sustainable use of AI, Indonesia needs to strengthen existing regulations, raise ethical awareness in society, and establish a dedicated regulatory body for AI technology.